Cooking parameters and some physic-chemical properties of rice composites as potential staple of Filipinos - Hurtada, W. A.; Barrion, A. S. A.; Rodriguez, F. M.; Nagares, N. D. L. (2003)
This study aimed to establish some physic-chemical properties of corn and the rice composites such as gelatinization temperature, gel consistency, and hardness as well as the cooking parameters namely, optimum water level, time, volume increase, water absorption and solubility index. Starch and amylose contents were also measured. Nine rice composites, ie., rice and corn combinations in varying proportions were evaluated. The study revealed that QPM white corn contains more amylose and starch resulting in higher ge consistency (length in mm) and hardness (kg/cm?) implying that as the proportion of corn increases in the composite, the harder or tougher it is when cooked. Increasing the amount of corn, specifically amylose in the composites also resulted in higher water absorption index and lower solubility index values though the later showed no significant difference. Thus, more water is needed and longer cooking time should be applied when cooking the rice composites. Amylose content seemingly was the major factor greatly influencing cohesiveness and tenderness during cooking. It is also the main parameter of cooking and eating quality of the rice composites.
Keywords: Cooking (Rice); Rice -- Quality